Calix[6]arene-based Brønsted acids for molecular recognition and catalysis. Issue 7 (27th January 2021) - Cera, Gianpiero; Cester Bonati, Federica; Bazzoni, Margherita; Secchi, Andrea; Arduini, Arturo
Abstract : A threading process and catalysis governed by trifluoromethylsulfonamide moieties are reported. Abstract : We report the synthesis of a versatile trifluoromethylsulfonamide calix[6]arene derivative with Brønsted acid features which can influence both molecular recognition and catalytic application. Indeed, in low polarity media, the trifluoromethyl-containing supramolecular wheel is able to respond to the complexation with charged species as a function of its selective ion-pair recognition. In parallel, the enhanced acidity is the key to promote Michael additions of indoles to nitroalkenes under pseudo -physiological reaction conditions (H2 O, 37 °C).